γ-6-phosphogluconolactone, a byproduct of the oxidative pentose phosphate pathway, contributes to AMPK activation through inhibition of PP2A - Gao, Xue (Mol Cell, 2019)
The oxidative pentose phosphate pathway (oxiPPP) contributes to cell metabolism through not only the production of metabolic intermediates and reductive NADPH, but also inhibition of LKB1-AMPK signaling by ribulose-5-phosphate (Ru-5-P), the product of the third oxiPPP enzyme 6-phosphogluconate dehydrogenase (6PGD). However, we found that knockdown of glucose-6-phosphate dehydrogenase (G6PD), the first oxiPPP enzyme, did not affect AMPK activation despite decreased Ru-5-P and subsequent LKB1 activation, due to enhanced activity of PP2A, the upstream phosphatase of AMPK. In contrast, knockdown of 6PGD or 6-phosphogluconolactonase (PGLS), the second oxiPPP enzyme, reduced PP2A activity. Mechanistically, knockdown of G6PD or PGLS decreased or increased 6-phosphogluconolactone level, respectively, which enhanced the inhibitory phosphorylation of PP2A by Src. Furthermore, γ-6-phosphogluconolactone, an oxiPPP byproduct with unknown function generated through intramolecular rearrangement of δ-6-phosphogluconolactone, the only substrate of PGLS, bound to Src and enhanced PP2A recruitment. Together, oxiPPP regulates AMPK homeostasis by balancing the opposing LKB1 and PP2A.